Implementation of the Book Ta’limul Muta’alim in Shaping the Character of Santri at Pondok Pesantren Darur Robbani Karanggede - Ikhsanuddin, Muhammad; Sukari, Sukari (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
Character education represents a cornerstone of Islamic educational philosophy, serving as a fundamental element in cultivating the holistic development of Muslim youth. In Indonesia's pesantren (Islamic boarding schools) tradition, character formation transcends conventional classroom instruction to become an integrated way of life that encompasses spiritual, intellectual, moral, and social dimensions. Character education is an important aspect in shaping the personality of students in the boarding school environment. The Ta'limul Muta'alim book has a central role in developing the character of santri by instilling the values of knowledge, patience, perseverance, and noble morals. This study aims to analyze the implementation of Ta'limul Muta'alim in shaping the character of students at Darur Robbani Karanggede Islamic Boarding School. The research method used is qualitative with a case study approach. Data collection techniques include observation, in-depth interviews, and documentation. The research findings show that Ta'limul Muta'alim is applied through formal teaching, daily practice, and examples from kyai and ustaz. Supporting factors include a conducive pesantren environment, practice-based learning methods, and a high level of discipline. However, the challenges faced include the diversity of santri backgrounds and the lack of initial understanding of the book. This study concludes that the implementation of Ta'limul Muta'alim is effective in shaping santri character, especially in the aspects of discipline, ethics, and responsibility. Therefore, it is very important for pesantren to continue to develop adaptive learning strategies to maximize the absorption of the values contained in this book.